Fabrication of Photomagnetic Carbon Surfaces via Redox Assembly - Y.-L. Song; C. M. Wang (Journal of Nanotechnology)
3-Aminophenylboronic acid (APBA) and the complex Ru(bpy)2(phendione)2+ (bpy = 2,2′-bipyridine, phendione = 1,10-phenanthroline-5,6-dione) were found to be useful building blocks for preparing photomagnetic carbon surfaces. Scanning tunneling microscopy (STM) showed that when APBA was diazotized in acidic sodium nitrite solutions and cathodically reduced with highly ordered pyrolytic graphite (HOPG) electrodes, nanoscale films formed on the electrodes. The resulting HOPG had strong affinities for phendione and Ru(bpy)2(phendione)2+ as the electrodes were biased in the presence of them, respectively, with voltages more negative than the cathodic peak potentials for phendione/phendiol and Ru(bpy)2(phendione)2+/Ru(bpy)2(phendiol)2+ (phendiol = 1,10-phenanthroline-5,6-diol). However, if APBA was excluded, the affinities did not exist. Boronate ester formation featured prominently in these intermolecular interactions. The average increments in the HOPG surface roughness contributed by APBA and Ru(bpy)2(phendione)2+ were roughly 1 : 2, suggesting that the reaction stoichiometry between APBA and Ru(bpy)2(phendione)2+ be 1 : 1. Ru(bpy)2(phendione)2+ could also be grafted to carbon nanotubes (CNTs) under conditions similar to those for the HOPG using ascorbate as sacrificial donor. The resulting CNTs and HOPG exhibited photomagnetism when exposed to the 473 nm light. The ruthenium complex was shown to be a room-temperature photomagnetism precursor, and APBA was shown to be an effective molecular bridge for the complex and carbon substrates.